The Implementation of Customer Relationship Management (CRM) Supported by SMS Gateway Technology - Winatha, Komang Redy (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Responding to the higher restaurant industry competition, the Mailaku Roemah Nongkrong restaurant was not too flexible in facing an environmental changes. It was still using manual technology while there was an advancing technological developments. It was still applying the internal resources for business development. One way to overcome this problem is by utilizing technology and the concept of customer relationship management (CRM). CRM is a marketing strategy to create and maintain customer relationships and reduce the possibility of customers moving to other competitors. This study presented the development and implementation of CRM in a web-based system that was supported by sms gateway technology. The research methodology that will be used in this study consists of some steps, such as library study, observation, interviews, and system development which was divided into analysis, design, coding, and testing. The result was a web-based system was able to manage customer data, product promotion, and customer service management to create good relationships with customers. This system can be as an alternative for restaurants and customers in establishing practical business communication.